FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 PERIODE 2015-2017 - Puspita, Erna; Kusumaningtyas, Dian (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2019)
This research is motivated by the importance of information about earnings needed by internal and external parties. So there are many factors that influence managers to manipulate company profit information. In this case the audit quality of the financial statements is an important factor because it is able to minimize the existence of corporate earnings management practices, so that the audit results on financial statements are reasonable. The purpose of this study was to determine whether earnings management is influenced by ownership mechanism variables and managerial skills, the level of financial statement disclosure, and also the intermediary variable in the form of audit quality. This research is a quantitative research with expost facto research technique. The population in this study is 34 companies. The sampling technique was purposive sampling. Data analysis techniques using Path Analysis. Research Results Testing the first model hypothesis, it can be concluded that managerial ownership, managerial skills, level of financial statement disclosure, and audit quality have a significant effect on earnings management. Testing the second model hypothesis, it can be concluded that managerial ownership, managerial skills, and the level of financial statement disclosure have a significant effect on audit quality. Based on the path analysis diagram, it can be concluded that the indirect effect of managerial ownership variables, managerial skills, and the level of financial statement disclosure through audit quality variables is greater than the direct influence.